Diagnostic, prognostic, and immunological roles of FUT8 in lung adenocarcinoma and lung squamous cell carcinoma - Zhijun Li; Zhenpeng Zhu; Peng Wang; Chenyang Hou; Lijuan Ren; Dandan Xu; Xiran Wang; Fei Guo; Qingxue Meng; Weizheng Liang; Jun Xue; Xuejun Zhi (PLoS ONE, 2025)
Lung cancer remains the leading cause of malignant tumors worldwide in terms of the incidence and mortality, posing a significant threat to human health. Given that distant metastases typically occur at the time of initial diagnosis, leading to a poor 5-year survival rate among patients, it is crucial to identify markers for diagnosis, prognosis, and therapeutic efficacy monitoring. Abnormal glycosylation is a hallmark of cancer cells, characterized by the disruption of core fucosylation, which is predominantly driven by the enzyme fucosyltransferase 8 (FUT8). Evidence indicates that FUT8 is a pivotal enzyme in cancer onset and progression, influencing cellular glycosylation pathways. Utilizing bioinformatics approaches, we have investigated FUT8 in lung cancer, resulting in a more systematic and comprehensive understanding of its role in the disease’s pathogenesis. In this study, we employed bioinformatics to analyze the differential expression of FUT8 between LUAD and LUSC. We observed upregulation of FUT8 in both LUAD and LUSC, associated with unfavorable prognosis, and higher diagnostic utility in LUAD. GO/KEGG analysis revealed a primary association between LUAD and the spliceosome. Immunologically, FUT8 expression was significantly associated with immune cell infiltration and immune checkpoint activity, with a notable positive correlation with M2 macrophage infiltration. Our analysis of FUT8 indicates that it may serve as a potential biomarker for lung cancer diagnosis and prognosis, and could represent a therapeutic target for LUAD and LUSC immunotherapy.